Pursuit of communal values in an agentic manner: a way to happiness? - Abele, Andrea E. (Frontiers in Psychology, 2014)
The present research studies the association between traits, values and life satisfaction. While values should influence the direction of an individual’s goals and behaviour, his/her traits impact effort expenditure, efficiency and persistence in goal-pursuit. We apply the framework of the “Big Two” of agency and communion (Bakan, 1966) for distinguishing the content of values and traits. While agentic content refers to qualities relevant for goal-attainment, such as assertiveness, competence or persistence, communal content refers to qualities relevant for the establishment and maintenance of social relationships, such as being friendly, helpful, or fair. We predict that high scores on communal values and high scores on agentic traits are associated with life satisfaction. We test these predictions in two studies conducted in different countries (Germany and Russia) with different cultural background. The findings support our reasoning: Across both countries we find positive associations of communal values and agentic traits with life satisfaction; and individuals high in communal values and high in agentic traits are most satisfied with their lives. In Russia, the association of communal values with life satisfaction is moderated by agentic traits; in Germany, however, there is a main effect of communal values.